ZAMANAGÓY SPORT MEDICINASÍNÍŃ JOQARÍ TÁJIRIYBELI SPORTSHÍLARDÍ TAYARLAWDA MEDICINALÍQ HÁM BIOLOGIYALÍQ ÁHMIYETI - Utepbergenov, A.K.; Mamutov, P.J. (SCIENCE and SOCIETY, 2022)
The article analyzes and names the main reasons why sports medicine has not become an official full-fledged independent area of science and practice that meets the requirements of sports. Its goals, objectives and main components are defined. A way of creating a modern service for medical and biological support for the training of qualified sportsmen is proposed. The global shortcomings of modern medical-biological and sports-pedagogical university education are revealed. Directions for solving existing problems in the field of higher sports and sports medical education are indicated. Certain shortcomings of the current organization of medical support in professional sports clubs are noted and ways to correct them are indicated.